2005
DOI: 10.1562/2004-11-30-ra-386r.1
|View full text |Cite
|
Sign up to set email alerts
|

Induced and Photoinduced DNA Damage by Quinolones: Ciprofloxacin, Ofloxacin and Nalidixic Acid Determined by Comet Assay¶

Abstract: Quinolones are degraded by light with loss of their antimicrobial activity, generating active species or radicals. Evidence exists that some fluoroquinolones (lomefloxacin, fleroxacin and enoxacin) induce damage to the cellular membrane and DNA cleavage by photosensitization. In this study, the genotoxic potential of the quinolones ofloxacin, nalidixic acid and ciprofloxacin (three antimicrobials frequently used in therapy) was evaluated upon irradiation with UV light by using the comet assay on cells of the J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…superoxide radical anion, hydroxyl radical, singlet oxygen) has been confirmed upon irradiation of lomefloxacin, enoxacin, ofloxacin and ciprofloxacin (16,20,21), but no correlation has been found between singlet oxygen generation and phototoxic impact (21). The potential photoreactivity channels of fluoroquinolone drugs have been discussed in the literature and it has been shown that not only the formation of singlet oxygen as a primary reactive species causing DNA‐photosensitized oxidation (20–22), but also triplet energy transfer appears to be mostly responsible for the phototoxic effects of fluoroquinolones (23).…”
Section: Introductionmentioning
confidence: 99%
“…superoxide radical anion, hydroxyl radical, singlet oxygen) has been confirmed upon irradiation of lomefloxacin, enoxacin, ofloxacin and ciprofloxacin (16,20,21), but no correlation has been found between singlet oxygen generation and phototoxic impact (21). The potential photoreactivity channels of fluoroquinolone drugs have been discussed in the literature and it has been shown that not only the formation of singlet oxygen as a primary reactive species causing DNA‐photosensitized oxidation (20–22), but also triplet energy transfer appears to be mostly responsible for the phototoxic effects of fluoroquinolones (23).…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced Comet formation has been revealed with ENO (62), RUF (70,71), FLE (93), NOR (62,93), BAY (93,106), SPA (112,121), LOM (62,93,94,105,106,122,123), CLI (122), CIP (93,122,124) and OFL (62,112). This latter was shown inefficient by other authors (124). Repair enzymes in Comet assay have revealed purine bases oxidations through formation of Fpg‐sensitive sites on tumoral cells photosensitized by ENO, LOM, OFL and NOR (62).…”
mentioning
confidence: 99%
“…Studies using rats treated with therapeutic doses of fluoroquinolones confirmed the observation in humans regarding the adverse effect of fluoroquinolones on spermatogenesis. 23 Changes observed on light microscope include expansion of interstitial and intertubular space with vacuolization, degeneration and necrosis of interstitial (leydig) cells following which an exudation into the interstitium was developed and congestion in veins increased in all experimental groups as compared to control groups showing P value < 0.05 that is significant. Multiple comparison among study groups showed that Ciprofloxacin produced less morphological changes (Fig.…”
Section: Discussionmentioning
confidence: 88%